Thomas Jefferson the art of power - Meacham, Jon (New York Random House Large Print, 2012)
In this magnificent biography, the Pulitzer Prize?winning author of American Lion and Franklin and Winston brings vividly to life an extraordinary man and his remarkable times. Thomas Jefferson: The Art of Power gives us Jefferson the politician and president, a great and complex human being forever engaged in the wars of his era. Philosophers think; politicians maneuver. Jefferson?s genius was that he was both and could do both, often simultaneously. Such is the art of power.
Includes bibliographical references (pages [1181]-1270)
Keywords: Presidents-United States-Biography.